Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 1110 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Platybelone argalus (Lesueur, 1821)" ] } The dataset includes 1110 records from 52 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003729-150410134957023/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences